TURİZMDE ATLI SPOR KÜMELENMESİ: DADAY ÖRNEĞİ - Aydoğan AYDOĞDU (Fırat University, 2019)
There were huge differences between rural areas and cities regarding living conditions and other opportunities after industrial revolution. In progress of time, a lot of modals and approaches were suggested so as to develop rural areas and eliminate those differences getting deep in favour of cities. Among those approaches, distinctive characteristics of locals came into prominence in regional and rural development. Recently, rural tourism activities have been one of prominent facts for eliminating regional differences because of being able to use distinctive sources. In addition this sustainability in tourism activities that have tough competition is another important fact for being dominant. Aim of this study is to analyze riding clusters that has been focused in Daday –district of Kastamonu- and central villages close to Daday. Qualitative methods have been applied and clusters consisting of touristic facilities given riding opportunities are analyzed. Results of the study present that touristic facilities given riding opportunities in Daday district of Kastamonu are a cluster example geographically.